Effects of problem solving and interpersonal skills training on violent behaviour among secondary school students in Delta State, Nigeria (2016)
Secondary school students in Delta State are increasingly engaging in violence which negatively affects their academic performance and health. Introduction of life skill into secondary curriculum is an effort at changing negative behaviour of students. However, previous studies have shown non-implementation of life skill training included in the school curriculum; hence the continued occurrence of violence among secondary schools students. This study therefore determined the effects of Life skill (problem solving and interpersonal skills) training on violent behaviour among secondary school students in Della State. A pre-test-post-lest control group quasi-experimental research design was adopted in this study. Simple random sampling technique was used to select one local government area from each of the three senatorial districts. Purposive sampling technique was used to select one co-educational school each from the selected three local government areas. Three secondary schools were randomly assigned to two experimental groups and control group. A sample of two hundred and sixteen students was used in the study. Four research hypotheses were tested at 0.05 alpha level. Data collected were analysed using ANCOVA. bindings revealed that, there was a significant mam effect of treatment on violent behaviour among secondary school students in Della state F(2,204-34.67)- There were no significant main effects of gender and religion on violent behaviour. Based on the findings, it was recommended that secondary school students should be exposed to problem solving and interpersonal skills which are components of life-skills regardless of gender and religion